PERILAKU SEKSUAL DITINJAU DARI PEMAHAMAN KONSEP REPRODUKSI MANUSIA, PERHATIAN ORANG TUA DAN JENIS KELAMIN SISWA KELAS III SEMESTER GASAL SMA NEGERI 5 SURAKARTA TAHUN PELAJARAN 2004/2005 (SEXUAL BEHAVIOUR ON 3RD GRADE STUDENT OF SMAN 5 SURAKARTA (ACADEMIC YEAR 2004-2005) IN PERSPECTIVES OF THEIR UNDERSTANDING TOWARD HUMAN REPRODUCTION, PARENTAL CARES AND SEXES) - Slamet Santoso (Bioedukasi: Jurnal Pendidikan Biologi, 2006)
The aims of this research are to know the influence of (1) human reproduction understanding (2) parental cares, (3) sexes and (4) interaction of each factor toward the sexual behavior of the students. The method used in this research was descriptive-quantitative method by expost facto. Research was carried out upon 3 rd grade students of SMA N 5 Surakarta as the population that sampled. The sampling technique used was random sampling technique which sampled 120 students. The data collected by using evaluation (test) method, documentation and anquette and analyzed by using analyses of variance.Statistical results showed that (1) the influence of human reproduction understanding toward sexual behavior is (Fo > Ft = 5.23 > 5.18), (2) parental cares toward sexual behavior is ( Fo > Ft = 12.654 > 5.18), (3) sexes toward sexual behavior is ( Fo > Ft = 70.712 > 5.18), (4) interaction between human reproduction understanding and parental cares toward sexual behavior is ( Fo > Ft = 5.666 > 5.18), (5) interaction between human reproduction understanding and sexes toward sexual behavioris ( Fo > Ft = 7.701 > 5.18), (6) interaction between parental cares and sexes toward sexual behavior is ( Fo > Ft = 10.295 > 5.18), (7) interaction among the three factors toward sexual behavior is ( Fo> Ft = 5.364 > 5.18).The aims of this research are to know the influence of (1) human reproduction understanding (2)parental cares, (3) sexes and (4) interaction of each factor toward the sexual behavior of the students.The method used in this research was descriptive-quantitative method by expost facto. Research wascarried out upon 3 rd grade students of SMA N 5 Surakarta as the population that sampled. The samplingtechnique used was random sampling technique which sampled 120 students. The data collected by usingevaluation (test) method, documentation and anquette and analyzed by using analyses of variance.Statistical results showed that (1) the influence of human reproduction understanding toward sexualbehavior is (Fo > Ft = 5.23 > 5.18), (2) parental cares toward sexual behavior is ( Fo > Ft = 12.654 > 5.18), (3)sexes toward sexual behavior is ( Fo > Ft = 70.712 > 5.18), (4) interaction between human reproductionunderstanding and parental cares toward sexual behavior is ( Fo > Ft = 5.666 > 5.18), (5) interaction betweenhuman reproduction understanding and sexes toward sexual behavioris ( Fo > Ft = 7.701 > 5.18), (6) interactionbetween parental cares and sexes toward sexual behavior is ( Fo > Ft = 10.295 > 5.18), (7) interaction among thethree factors toward sexual behavior is ( Fo> Ft = 5.364 > 5.18).